Scientific trips between Andalusia and the Mashreq province (Khorasan and Transoxiana): The unity of culture and the The privacy of creativity 316- 620928-1223 m/ e - ben Kheira, Najib (Al-Adab Journal, 2020)
The Scientific trips is a noble manifestation in the Arab-Islamic culture, where people continue to exchange trips, and take from the sources of science, And to meet the scholars K , And residence in the capitals of science to stay in the cities of science and thought centers in the Islamic Mashreq (Khorasan and Transoxiana) sometimes or in the country of Andalusia at other times. During the period of study (316-620 / 928-1223) This study dealt with the following points: Introduction Scientific trips Civilizational Behavior  The motives of the Scientific trips between the passion of Maghreb ’ and Charisma of the Orient Image of scientific trips (book trip- model) Scholars traveled from Andalusia to Khorasan and Transoxiana  Scholars traveled from Khorasan and and Transoxiana to Andalusia Conclusion: Results and Notes